A model protocol for the cryopreservation and recovery of motile lizard sperm using the phosphodiesterase inhibitor caffeine. Issue 1 (22nd June 2020) - Campbell, Lachlan; Cafe, Shenae L; Upton, Rose; Doody, J Sean; Nixon, Brett; Clulow, John; Clulow, Simon
Abstract: Reproductive technologies such as genome storage and assisted reproduction have a significant role to play in ending or reversing species extinctions. However, such technologies for non-model organisms (i.e. non-mammalian species) are poorly developed. This is particularly true for the reptiles, in which there is a dearth of successful protocols for cryopreserving reptile spermatozoa, despite limited attempts. We investigated sperm cryopreservation in the Australian lizard Varanus panoptes with the objective of addressing the unmet need for an optimized cryopreservation protocol for the spermatozoa of squamate reptiles. We tested the efficacy of two cryoprotectants [dimethyl sulfoxide (DMSO) and glycerol] as well supplementation with a phosphodiesterase inhibitor (caffeine) to promote post-thaw motility. For cryopreservation, sperm were cooled in straws suspended in liquid nitrogen vapour for 5 minutes (approximately −135°C), before being plunged into liquid nitrogen (approximately −196°C), and later thawed in a water bath at 35°C. Samples were incubated post-thaw for 10 minutes in the presence or absence of 10 mM of caffeine. Both cryoprotectant type and concentration significantly affected percent sperm motility pre-freezing, with DMSO being less cytotoxic than glycerol and motility decreasing at higher concentrations of both cryoprotectant types. While cold shock did not significantly affect sperm motility, both cryoprotectant type and concentration did significantly impact the motility of post-thawed spermatozoa. Thus, mid-range concentrations (10% v/v) of DMSO and glycerol yielded a greater post-thaw motility compared with 5 and 20% v/v, while DMSO proved superior to glycerol. The addition of caffeine resulted in a significant recovery of post-thaw motility for both cryoprotectants, with higher rates of motility being associated with higher cryoprotectant concentrations. These protocols provide a significant step forward for in situ and ex situ management of threatened reptiles and add to recent evidence that reptilian sperm may have the full range of phosphorylation-mediated cellular mechanisms associated with capacitation, motility and metabolic regulation found in mammalian sperm.